PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PEMBIAYAAN YANG TERDAFTAR DI BEI - Ni Ketut Sulastri; Ni Ketut Surasni; Hermanto Hermanto (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
This study aimed to analyze the effect of profitability on capital structure, the influence of capital structure on firm value, the effect of profitability on firm value and analyze the effect of profitability on firm value through capital structure on finance companies on the IDX. Data analysis technique in this study is Path Analysis and tools of analysis used are IBM SPSS 23. The results of the study show that (1) profitability has a positive and not significant effect on capital structure (2) capital structure has a positive and not significant effect on firm value (3 ) profitability has a positive and significant effect on firm value (4) capital structure is not able to mediate the effect of profitability on firm value.